Can serum granulocyte-macrophage colony-stimulating factor and CCL17 levels be a marker of disease activation in spondyloarthritis? - Rezan Koçak Ulucaköy; Ayza Kılıç; Sevilay Batıbay; İdil Melis Çobanoğlu and Elif Nur Yıldırım Öztürk and Zafer Günendi and Aylin Sepici Dinçel and Feride Nur Göğüş (Archives of Rheumatology, 2024)
Objectives: The aim of this cross-sectional study was to investigate if serum levels of granulocytemacrophage colony-stimulating factor (GM-CSF) and CC chemokine ligand 17 (CCL17) correlate with disease activity in axial spondyloarthritis (axSpA) and peripheral spondyloarthritis (pSpA) patients. Patients and methods: The cross-sectional study was conducted with 80 individuals (48 females, 32 males; mean age: 47.7±11.5) between March 2021 and September 2021. Of the participants, 20 were axSpA, 20 were pSpA, and 20 were active rheumatoid arthritis patients, and the remaining 20 were healthy controls. Age, sex, body mass index, disease duration, comorbid diseases, smoking status, medical treatments, C-reactive protein (CRP) level and human leukocyte antigen B27 (HLA-B27) positivity were recorded. Serum GM-CSF and CCL17 levels were analyzed by ELISA. Ankylosing Spondylitis Disease Activity Score with CRP (ASDAS-CRP) was used to evaluate the disease activity of patients with spondyloarthritis. Functional status of spondyloarthritis patients was evaluated by Bath Ankylosing Spondylitis Functional Index (BASFI). Results: While the serum GM-CSF levels were similar in the axSpA and pSpA groups, they were significantly higher than the healthy control group (p=0.021 and p=0.009, respectively). There was a significant correlation between GM-CSF levels and ASDAS-CRP (r=0.545, p=0.013) and BASFI (r=0.546, p=0.013) in the axSpA group. In active axSpA patients, the cut-off value for GM-CSF was 15.89 pg/mL (sensitivity 50%, specificity 100%). No differences were detected in serum CCL17 levels among the groups. Conclusion: The results suggest that serum GM-CSF levels may be used as a new marker for the evaluation of disease activity in axSpA, and GM-CSF might be a therapeutic target.